The Tibet factor and India - China relations - Pokharna, Bhawana (2009)
The recent uprising in Tibet has once again brought the question of Tibet into the limelight. The unrest in Tibet just prior to Olympic games in Beijing put the Chinese leadership in perturbing situation. It evoked international responses in favour of Tibetans which resulted into bycotting of Olympic torch relay ceremony by many countries' leaders, people and celebrities. The massive international support received by Tibetans put the Chinese leadership in defensive position and forced them to invite Tibetan representatives for talks, however the talks remained inconclusive. Since the presence of Dalai Lama in India. Tibet is a very sensitive issue between India and China. Therefore present paper aims to analyse Tibet in historical perspective as well as the impact of Tibet factor on India - China relations. - Reproduced.
Keywords: India - Foreign relations - China; Violence - Tibet; Violence